Nanomaterials for Chemical Engineering (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Scientists and engineers have emphasized the study of nanomaterials in recent decades. By having superior properties, nanomaterials are helping to greatly improve and even revolutionize the development of various technology and industry sectors. Despite many advantages, there are challenges present in the control and design of nanomaterials with specific properties (e.g., morphology, size, porosity, conductivity, optical property, photoelectric property, chemical activity, etc.) to meet with their functional aims. The main applications of nanomaterials in the chemical engineering area are catalyst, coating, adsorption, sensor, drug delivery, etc., which all have fascinating yet challenging research topics.This reprint collects original research papers and comprehensive review papers that cover the topics of development of novel nanomaterials and synthesis methods, experimental characterization and computational modelling studies, as well as exploitation in devices and practical applications, hoping to bring new insights into the chemical engineering area.